Medical education in the USA--adult-friendly? - Whitehouse, A. (BMJ Group, 1998)
In the United States of America, the Area Health Education Center (AHEC) system of training residents has allowed high-quality postgraduate education to flourish. This paper describes the evolution of the AHECs in the context of medical education over the past 50 years. The arrangements for programme administration and design, resident assessment and appraisal, training of trainers in educational methods, and the accreditation of training programmes are discussed. The fast-evolving UK postgraduate education scene can learn some useful lessons from the US system.